Posttransplant Classic Hodgkin Lymphoma: Richter Transformation or Posttransplant Lymphoproliferative Disorder?. Issue 5 (September 2019) - Lee, Ina; Zou, Ying; Hodges, Susan; Rapoport, Aaron P.; Hardy, Nancy; Singh, Zeba
Abstract : Abstract: Richter transformation (RT) is defined as the transformation of chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) into high-grade lymphoma. An average of 5% of patients with CLL/SLL will have disease that undergoes RT during their clinical course. While most (75%) of these transformed cases manifest as diffuse large B-cell lymphoma, other variants occur, including a small minority (0.4%–0.7%) that progress to a classic Hodgkin lymphoma variant. Richter transformation portends a poor outcome in comparison to nontransformed CLL/SLL. Allogeneic stem cell transplantation (allo-SCT) can be offered, with a 5-year survival rate of 50% to 70%. In addition to disease relapse, transplantation carries significant risk of nonrelapse morbidity, including posttransplant lymphoproliferative disorder (PTLD). The distinction between disease progression or recurrence and PTLD can be challenging and has critical prognostic and therapeutic implications. In this report, we describe a patient whose initial CLL/SLL transformed to diffuse large B-cell lymphoma, who then received allo-SCT. Subsequent development of classic Hodgkin lymphoma proved to be a diagnostic conundrum, for which PTLD and disease progression/recurrence were both reasonable considerations. This case illustrates the diagnostic dilemma and semantic confusion faced by both pathologists and clinicians when lymphoproliferative disorders emerge within the immunologically complex interface of CLL/SLL, RT, and allo-SCT. As molecular technologies are becoming more commonplace in routine diagnostics, subpopulation clonal analysis may be useful in such cases. It may also be worth reevaluating the classification and criteria for PTLD and different subtypes of RT, especially in light of implications for prognosis and optimal therapies.